2016
DOI: 10.1016/j.socnet.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the relation between young immigrants’ host country identification and their friendships with natives

Abstract: Immigrants who strongly identify with the host country have more native friends than immigrants with weaker host country identification. However, the mechanisms underlying this correlation are not well understood. Immigrants with strong host country identification might have stronger preferences for native friends, or they might be more often chosen as friends by natives. In turn, having native friends or friends with strong host country identification might increase immigrants' host country identification. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
44
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 72 publications
7
44
0
Order By: Relevance
“…Ethnic majority students' preference for dual over heritage‐country identifiers suggests that they accept some maintenance of heritage country identification as long as this is accompanied by host country identification. Accordingly, by tendency, ethnic majority adolescents also preferred ethnic minority peers with host country identification to those with heritage country identification, which confirms earlier findings (Leszczensky et al., ). Our findings thus differ from Boda and Néray () who found that non‐Roma Hungarian ethnic majority adolescents disliked ethnic minority Roma adolescents, irrespective of the Roma students' ethnic self‐identification.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Ethnic majority students' preference for dual over heritage‐country identifiers suggests that they accept some maintenance of heritage country identification as long as this is accompanied by host country identification. Accordingly, by tendency, ethnic majority adolescents also preferred ethnic minority peers with host country identification to those with heritage country identification, which confirms earlier findings (Leszczensky et al., ). Our findings thus differ from Boda and Néray () who found that non‐Roma Hungarian ethnic majority adolescents disliked ethnic minority Roma adolescents, irrespective of the Roma students' ethnic self‐identification.…”
Section: Discussionsupporting
confidence: 89%
“…Overall, our results imply that in the domain of adolescent friendship relations there are benefits to an ethnic self‐identification that includes the host country and that there are costs to an ethnic self‐identification based exclusively on ethnic heritage. While the finding that ethnic majority adolescents prefer ethnic minority peers with host country identification is in line with previous research (Leszczensky et al., ), the drawbacks of heritage country identification for relations to other ethnic minority peers represent a novel finding. This finding is particularly important given that inter‐minority relations (i.e., relationships between different ethnic minority groups) are still an under‐researched topic (Koops et al., ).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations